Pendidikan Kesehatan dalam Rangka Mitigasi dan Adaptasi Menghadapi Wabah Covid-19 di Kabupaten Buton Selatan Provinsi Sulawesi Tenggara - Nur Illiyyin Akib; Halik Halik; Ruslin Ruslin; Muamal Gadapi (Jurnal Pengabdian UntukMu NegeRI, 2021)
Thematic KKN- Thematic Social Work Internship have been carried out in the form of health education for the community in South Buton Regency. This activity aims to increase understanding of health in the context of handling the Corona Virus Disease 19 (Covid-19) outbreak. This activity was carried out in several villages in South Buton Regency. Activities were carried out from June to July 2020. Implementation of activities consisted of counseling on the Gerakan Masyarakat Hidup Sehat (Germas), counseling on the tanaman Obat Keluarga (Toga), and counseling on Perilaku Hidup Bersih dan Sehat (PHBS), as well as disseminating information through social media and mass media. Extension is carried out by lecturing, practice, and question and answer methods. The social media used is Instagram. The mass media used are leaflets. This activity succeeded in increasing understanding of health for the community in South Buton Regency